High-strength concrete and preparation method thereof

By optimizing the cement variety and content in high-strength concrete, adding mineral blends, nanomaterials and reinforced fibers, the problem of insufficient strength and durability of traditional concrete in structures such as high-rise buildings has been solved, and high strength and high durability have been achieved. High-strength concrete preparation with good working properties reduces the preparation cost.

CN119430795APending Publication Date: 2025-02-14SUZHOU JIASHENG WANCHENG CONSTR IND CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411578804.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and discloses high-strength concrete and a preparation method thereof.The high-strength concrete is prepared from, by weight, 350-500 parts of cement, 100-250 parts of mineral admixture, 600-800 parts of fine aggregate, 1000-1200 parts of coarse aggregate, 5-15 parts of high-performance water reducing agent, 10-30 parts of reinforced fiber, 5-20 parts of nanometer material and 150-200 parts of water; stirring the coarse aggregate and the fine aggregate for 30-60 seconds to uniformly mix the coarse aggregate and the fine aggregate; then premixing the cement, the mineral admixture and the nano material at 100-200r / min for 2-3 minutes, and performing ultrasonic treatment at the same time; and then the mixed powder and the aggregate are stirred for 60-90 seconds at the speed of 200-300 r / min. Adding water into a high-performance water reducing agent to prepare a solution, adding the solution and the dispersed reinforced fibers into a stirrer, and stirring for 120-180 seconds at the speed of 300-400r / min; and standing the mixture at 30-40 DEG C for 1-2 hours, stirring at a low speed during the period, and curing for not less than 28 days at 20 + / -2 DEG C and the humidity of not less than 95%. The invention has the advantages of high strength, high durability and good workability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to high-strength concrete and a preparation method thereof. Background Art

[0002] With the development of modern construction technology, the strength requirements for concrete are getting higher and higher. In the construction of large-scale infrastructure such as high-rise buildings, long-span bridges, and marine engineering, traditional concrete can no longer meet the structural requirements for strength, durability and other properties.

[0003] At present, ordinary concrete has problems such as low compressive strength and poor durability. On the one hand, the limitations of cement varieties and quality make the early strength of concrete develop slowly and the final strength is not high. On the other hand, problems such as unreasonable aggregate grading and high mud content also affect the overall performance of concrete. In addition, although there are some studies on high-strength concrete, there are often defects such as complex preparation process, high cost, or sacrificing the workability of concrete while improving strength. For example, some high-strength concretes are prone to segregation during the mixing process, or require the use of special and expensive additives, which limits the widespread application of high-strength concrete. Therefore, it is of great practical significance to develop a high-strength concrete with excellent performance, reasonable preparation process and controllable cost. Summary of the invention

[0004] In order to solve the above-mentioned problems, the present invention proposes a high-strength concrete with high strength, high durability and good workability and a preparation method thereof.

[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is: a high-strength concrete, comprising the following components, by weight: 350-500 parts of cement, 100-250 parts of mineral admixture, 600-800 parts of fine aggregate, 1000-1200 parts of coarse aggregate, 5-15 parts of high-performance water reducing agent, 10-30 parts of reinforcing fiber, 5-20 parts of nanomaterial and 150-200 parts of water.

[0006] Preferably, the cement is silicate cement with a strength grade of not less than 52.5 and a specific surface area of ​​not less than 350 m 2 / kg, the standard value of 28-day compressive strength is not less than 52.5MPa, the C3S content of the cement is 50%-65%, and the C2S content is 15%-30%.

[0007] Preferably, the mineral admixture comprises fly ash, slag powder and silica fume, wherein the fly ash is Class I fly ash, the water requirement ratio is not more than 95%, and the fineness is not more than 12%; the specific surface area of ​​the slag powder is not less than 400m 2 / kg, the activity index is not less than 75% in 7 days and not less than 95% in 28 days; the SiO2 content of silica fume is not less than 90%, and the specific surface area is not less than 15000m 2 / kg, and the weight ratio of fly ash, slag powder and silica fume is 3:5:2.

[0008] Preferably, the fine aggregate is medium sand with a fineness modulus of 2.6-3.0, a mud content of no more than 2%, a mud block content of no more than 0.5%, a mica content of no more than 1%, a light material content of no more than 1%, a sulfide and sulfate content of no more than 0.5%, and a strength index mass loss rate of no more than 8%.

[0009] Preferably, the coarse aggregate is continuously graded crushed stone with a particle size of 5-25 mm, a crushing index of no more than 10%, a needle-like particle content of no more than 5%, a mud content of no more than 0.5%, a mud block content of no more than 0.2%, and a rock compressive strength of no less than 1.5 times the concrete strength grade.

[0010] Preferably, the high-performance water-reducing agent is a polycarboxylic acid-based high-performance water-reducing agent, with a water reduction rate of not less than 25%, an air content of not more than 3%, a slump change over time of not more than 20 mm in 1 hour, and a compressive strength ratio of not less than 130%.

[0011] Preferably, the reinforcing fiber is a short chopped basalt fiber with a length of 6-12 mm, a single filament diameter of 13-15 μm, a tensile strength of not less than 3000 MPa, an elastic modulus of not less than 90 GPa, an elongation at break of not more than 3.1%, and the fiber surface is treated with a coupling agent.

[0012] Preferably, the nano material is a mixture of nano silicon dioxide and nano calcium carbonate, the particle size of the nano silicon dioxide is 10-50 nm, the particle size of the nano calcium carbonate is 20-80 nm, the weight ratio of the two is 2:3, and the purity of the nano material is not less than 95%.

[0013] A method for preparing high-strength concrete comprises the following steps:

[0014] Step 1: Put the coarse aggregate and fine aggregate into the mixer and stir for 30-60 seconds to mix the aggregates evenly;

[0015] Step 2: premixing cement, mineral admixture and nanomaterial in another stirring device for 2-3 minutes at a premixing speed of 100-200 r / min to obtain a mixed powder; during the premixing process, ultrasonic treatment is performed on the mixed powder at an ultrasonic frequency of 20-40 kHz, a power of 100-300 W, and an ultrasonic treatment time of 30-60 seconds;

[0016] Step 3: Add the mixed powder in step 2 into the mixer in step 1, and mix with the aggregate for 60-90 seconds at a stirring speed of 200-300 r / min;

[0017] Step 4: Add a high-performance water-reducing agent to water, stir evenly to form a solution, then add the solution and reinforcing fiber to a mixer at the same time, continue stirring for 120-180 seconds, and the stirring speed is 300-400r / min to obtain a high-strength concrete mixture; before adding the reinforcing fiber to the mixer, the reinforcing fiber is first dispersed, the dispersant is polyethylene glycol, the amount of the dispersant is 0.5%-1% of the weight of the reinforcing fiber, and the dispersion treatment time is 10-20 minutes;

[0018] Step 5: After the high-strength concrete mixture is allowed to stand at 30-40°C for 1-2 hours, it is molded and cured. The curing temperature is 20±2°C, the humidity is not less than 95%, and the curing time is not less than 28 days. During the standing process, the high-strength concrete mixture is stirred at a low speed every 30-45 minutes, the stirring speed is 50-100r / min, and the stirring time is 10-20 seconds.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] High strength: The present invention significantly improves the compressive strength of concrete by optimizing the type and content of cement, adding mineral admixtures, nanomaterials, and reinforcing fibers. According to tests, the 28-day compressive strength of the prepared high-strength concrete can reach more than 80MPa, which can meet the strict requirements of high-rise buildings, long-span bridges, etc. on structural strength.

[0021] High durability: The use of low water-binder ratio, high-quality aggregates, mineral admixtures and nanomaterials improves the density of concrete, effectively prevents the invasion of external harmful substances such as chloride ions and sulfate ions, reduces the permeability of concrete, and thus greatly improves the durability of concrete. In long-term tests simulating marine environments, the concrete of the present invention exhibits good corrosion resistance.

[0022] Good workability: The use of high-performance water-reducing agent ensures that the concrete still has good workability at low water-binder ratio and small slump loss. The uniform dispersion of reinforcing fibers also has no negative impact on the workability of concrete, allowing the concrete to maintain good fluidity and plasticity during mixing, transportation and pouring.

[0023] Cost-effectiveness: The present invention improves the performance of concrete while rationally selecting raw materials, such as using industrial waste slag as mineral admixtures, which reduces costs to a certain extent. Moreover, the preparation process is simple and easy, does not require special equipment and complicated operations, and is conducive to large-scale production and application. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below with reference to the embodiments.

[0025] Example 1

[0026] Raw material preparation

[0027] Cement: Use silicate cement with a strength grade of 52.5 and a specific surface area of ​​380m 2 / kg, the standard value of 28-day compressive strength is 55MPa, the C3S content is 60%, the C2S content is 20%, and 400 portions are weighed.

[0028] Mineral admixtures: fly ash is Class I fly ash, with a water requirement ratio of 90% and a fineness of 10%; the specific surface area of ​​slag powder is 420m 2 / kg, the activity index is 80% in 7 days and 98% in 28 days; the SiO2 content of silica fume is 92%, and the specific surface area is 16000m 2 / kg. According to the weight ratio of fly ash, slag powder and silica fume of 3:5:2, a total of 180 parts were weighed.

[0029] Fine aggregate: medium sand with fineness modulus of 2.8, mud content of 1.5%, mud block content of 0.3%, mica content of 0.8%, light matter content of 0.8%, sulfide and sulfate content (calculated as SO3) of 0.3%, and mass loss rate of firmness index of 6%. Weigh 700 parts.

[0030] Coarse aggregate: continuously graded crushed stone with a particle size of 5-25mm, a crushing index of 8%, a needle-like particle content of 3%, a mud content of 0.3%, a mud block content of 0.1%, and a rock compressive strength of 1.8 times the concrete strength grade. Weigh 1,100 portions.

[0031] High-performance water-reducing agent: polycarboxylic acid-based high-performance water-reducing agent, water reduction rate is 28%, air content is 2.5%, slump change over time of 1h is 15mm, compressive strength ratio (28 days) is 135%, weigh 10 parts.

[0032] Reinforcement fiber: chopped basalt fiber with a length of 8 mm, a single fiber diameter of 14 μm, a tensile strength of 3200 MPa, an elastic modulus of 95 GPa, an elongation at break of 2.8%, and the fiber surface is treated with a coupling agent. Weigh 20 portions.

[0033] Nanomaterials: The particle size of nano silicon dioxide is 30 nm, the particle size of nano calcium carbonate is 50 nm, the weight ratio of the two is 2:3, the purity of both is 96%, and a total of 12 parts are weighed.

[0034] Water: weigh 180 parts.

[0035] Preparation process

[0036] Place coarse aggregate and fine aggregate into a mixer and mix for 40 seconds.

[0037] The cement, mineral admixture and nanomaterials were premixed in another stirring device at a speed of 150 r / min for 2.5 minutes, and ultrasonic treatment was performed at the same time, with an ultrasonic frequency of 30 kHz, a power of 200 W and an ultrasonic treatment time of 40 seconds.

[0038] Add the premixed powder into the aggregate mixer and mix at 250r / min for 70 seconds.

[0039] After adding the high-performance water reducing agent into the water and stirring evenly, add it into the mixer together with the reinforcing fiber dispersed with polyethylene glycol (the amount of dispersant is 0.8% of the weight of the reinforcing fiber, and the dispersion treatment time is 15 minutes), and stir at a speed of 350r / min for 150 seconds.

[0040] The mixture was allowed to stand at 35°C for 1.5 hours, stirred at 80 r / min for 15 seconds every 40 minutes, and then cured at 20°C and 95% humidity for 28 days.

[0041] Example 2

[0042] Raw material preparation

[0043] Cement: Portland cement with strength grade 52.5 and specific surface area of ​​360m 2 / kg, 28-day compressive strength standard value 53MPa, C3S content 58%, C2S content 22%, weigh 380 parts.

[0044] Mineral admixtures: fly ash water requirement ratio 92%, fineness 11%; slag powder specific surface area 410m 2 / kg, activity index 78% in 7 days, 96% in 28 days; silica fume SiO2 content 91%, specific surface area 15500m 2 / kg, weigh a total of 160 portions according to the proportion.

[0045] Fine aggregate: medium sand with fineness modulus 2.7, mud content 1.8%, mud block content 0.4%, mica content 0.9%, light matter content 0.9%, sulfide and sulfate content (calculated as SO3) 0.4%, strength index mass loss rate 7%, weigh 680 parts.

[0046] Coarse aggregate: continuously graded crushed stone with a particle size of 5-25mm, crushing index of 9%, needle-like particle content of 4%, mud content of 0.4%, mud block content of 0.15%, rock compressive strength is 1.6 times the strength grade of concrete, weigh 1050 parts.

[0047] High-performance water-reducing agent: polycarboxylic acid-based high-performance water-reducing agent, water reduction rate 26%, air content 2.8%, slump change over time 1h 18mm, compressive strength ratio (28 days) 132%, weigh 8 parts.

[0048] Reinforcement fiber: 7 mm long chopped basalt fiber, single filament diameter 13.5 μm, tensile strength 3100 MPa, elastic modulus 92 GPa, elongation at break 3.0%, treated with coupling agent, weigh 18 parts.

[0049] Nanomaterials: Nano silicon dioxide particle size 25nm, nano calcium carbonate particle size 60nm, purity 95%, weigh 10 parts in total according to the proportion.

[0050] Water: weigh 170 parts.

[0051] Preparation process

[0052] The coarse and fine aggregates were mixed for 50 seconds.

[0053] Cement, mineral admixtures and nanomaterials were premixed at 180 r / min for 2 min, ultrasonic frequency of 25 kHz, power of 180 W, and ultrasonication for 50 s.

[0054] Add the powder into the aggregate mixer and mix at 280r / min for 80 seconds.

[0055] After adding water to the high-performance water reducing agent and stirring, the reinforcing fibers dispersed with polyethylene glycol (the amount of dispersant is 0.6% of the weight of the reinforcing fibers, and the dispersion time is 12 minutes) are added into a mixer and stirred at 380 r / min for 160 seconds.

[0056] The mixture was allowed to stand at 32°C for 1.8 hours, stirred at 70 r / min for 12 seconds every 35 minutes, and then cured at 20°C and 95% humidity for 28 days.

[0057] Example 3

[0058] Raw material preparation

[0059] Cement: Portland cement with strength grade 52.5 and specific surface area of ​​350m 2 / kg, 28-day compressive strength standard value 52.5MPa, C3S content 55%, C2S content 25%, weigh 350 parts.

[0060] Mineral admixtures: fly ash water requirement ratio 95%, fineness 12%; slag powder specific surface area 400m 2 / kg, activity index 75% in 7 days, 95% in 28 days; silica fume SiO2 content 90%, specific surface area 15000m 2 / kg, weigh 100 portions in total according to the proportion.

[0061] Fine aggregate: medium sand with fineness modulus 2.6, mud content 2%, mud block content 0.5%, mica content 1%, light matter content 1%, sulfide and sulfate content (calculated as SO3) 0.5%, strength index mass loss rate 8%, weigh 600 parts.

[0062] Coarse aggregate: continuously graded crushed stone with particle size of 5-25mm, crushing index of 10%, needle-like particle content of 5%, mud content of 0.5%, mud block content of 0.2%, rock compressive strength is 1.5 times the strength grade of concrete, weigh 1000 parts.

[0063] High-performance water-reducing agent: polycarboxylic acid-based high-performance water-reducing agent, water reduction rate 25%, air content 3%, slump change over time of 1h 20mm, compressive strength ratio (28 days) 130%, weigh 5 portions.

[0064] Reinforcement fiber: 6 mm long chopped basalt fiber, single filament diameter 13 μm, tensile strength 3000 MPa, elastic modulus 90 GPa, elongation at break 3.1%, treated with coupling agent, weigh 10 parts.

[0065] Nanomaterials: Nano silicon dioxide particle size is 10 nm, nano calcium carbonate particle size is 20 nm, the weight ratio of the two is 2:3, the purity of both is 95%, and a total of 5 portions are weighed.

[0066] Water: weigh 150 parts.

[0067] Preparation process

[0068] Place coarse aggregate and fine aggregate into a mixer and mix for 60 seconds.

[0069] The cement, mineral admixture and nanomaterials were premixed in another stirring device at a speed of 200 r / min for 3 minutes, with an ultrasonic frequency of 20 kHz, a power of 100 W and an ultrasonic treatment time of 60 seconds.

[0070] Add the premixed powder into the aggregate mixer and mix at 300r / min for 90 seconds.

[0071] After adding the high-performance water reducing agent into the water and stirring evenly, add it into the mixer together with the reinforcing fiber dispersed with polyethylene glycol (the amount of dispersant is 0.5% of the weight of the reinforcing fiber, and the dispersion treatment time is 10 minutes), and stir at a speed of 400r / min for 180 seconds.

[0072] The mixture was allowed to stand at 30°C for 2 hours, stirred at 50 r / min for 20 seconds every 45 minutes, and then cured at 20°C and 95% humidity for 28 days.

[0073] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high-strength concrete, characterized in that: The invention comprises the following components by weight: 350-500 parts of cement, 100-250 parts of mineral admixture, 600-800 parts of fine aggregate, 1000-1200 parts of coarse aggregate, 5-15 parts of high-performance water reducing agent, 10-30 parts of reinforcing fiber, 5-20 parts of nano material and 150-200 parts of water.

2. The high-strength concrete according to claim 1, characterized in that: The cement is silicate cement with a strength grade of not less than 52.5 and a specific surface area of ​​not less than 350m 2 / kg, the standard value of 28-day compressive strength is not less than 52.5MPa, the C3S content of the cement is 50%-65%, and the C2S content is 15%-30%.

3. The high-strength concrete according to claim 1, characterized in that: The mineral admixtures include fly ash, slag powder and silica fume, wherein the fly ash is Class I fly ash, the water requirement ratio is not more than 95%, the fineness is not more than 12%; the specific surface area of ​​the slag powder is not less than 400m 2 / kg, the activity index is not less than 75% in 7 days and not less than 95% in 28 days; the SiO2 content of silica fume is not less than 90%, and the specific surface area is not less than 15000m 2 / kg, and the weight ratio of fly ash, slag powder and silica fume is 3:5:

2.

4. The high-strength concrete according to claim 1, characterized in that: The fine aggregate is medium sand with a fineness modulus of 2.6-3.0, a mud content of no more than 2%, a mud block content of no more than 0.5%, a mica content of no more than 1%, a light material content of no more than 1%, a sulfide and sulfate content of no more than 0.5%, and a strength index mass loss rate of no more than 8%.

5. The high-strength concrete according to claim 1, characterized in that: The coarse aggregate is continuously graded crushed stone with a particle size of 5-25 mm, a crushing index of no more than 10%, a needle-like particle content of no more than 5%, a mud content of no more than 0.5%, a mud block content of no more than 0.2%, and a rock compressive strength of no less than 1.5 times the concrete strength grade.

6. The high-strength concrete according to claim 1, characterized in that: The high-performance water-reducing agent is a polycarboxylic acid-based high-performance water-reducing agent, with a water reduction rate of not less than 25%, an air content of not more than 3%, a slump change over time of not more than 20 mm in 1 hour, and a compressive strength ratio of not less than 130%.

7. The high-strength concrete according to claim 1, characterized in that: The reinforcing fiber is short-cut basalt fiber with a length of 6-12 mm, a single fiber diameter of 13-15 μm, a tensile strength of not less than 3000 MPa, an elastic modulus of not less than 90 GPa, an elongation at break of not more than 3.1%, and the fiber surface is treated with a coupling agent.

8. The high-strength concrete according to claim 1, characterized in that: The nano material is a mixture of nano silicon dioxide and nano calcium carbonate, the particle size of the nano silicon dioxide is 10-50nm, the particle size of the nano calcium carbonate is 20-80nm, the weight ratio of the two is 2:3, and the purity of the nano material is not less than 95%.

9. The method for preparing high-strength concrete according to claim 1, characterized in that: The following steps are involved: Step 1: Put the coarse aggregate and fine aggregate into the mixer and stir for 30-60 seconds to mix the aggregates evenly; Step 2: premixing cement, mineral admixture and nanomaterial in another stirring device for 2-3 minutes at a premixing speed of 100-200 r / min to obtain a mixed powder; during the premixing process, ultrasonic treatment is performed on the mixed powder at an ultrasonic frequency of 20-40 kHz, a power of 100-300 W, and an ultrasonic treatment time of 30-60 seconds; Step 3: Add the mixed powder in step 2 into the mixer in step 1, and mix with the aggregate for 60-90 seconds at a stirring speed of 200-300 r / min; Step 4: Add a high-performance water-reducing agent to water, stir evenly to form a solution, then add the solution and reinforcing fiber to a mixer at the same time, continue stirring for 120-180 seconds, and the stirring speed is 300-400r / min to obtain a high-strength concrete mixture; before adding the reinforcing fiber to the mixer, the reinforcing fiber is first dispersed, the dispersant is polyethylene glycol, the amount of the dispersant is 0.5%-1% of the weight of the reinforcing fiber, and the dispersion treatment time is 10-20 minutes; Step 5: After the high-strength concrete mixture is allowed to stand at 30-40°C for 1-2 hours, it is molded and cured. The curing temperature is 20±2°C, the humidity is not less than 95%, and the curing time is not less than 28 days. During the standing process, the high-strength concrete mixture is stirred at a low speed every 30-45 minutes, the stirring speed is 50-100r / min, and the stirring time is 10-20 seconds.

Citation Information

Cited By

  • High-strength concrete prefabricated part and preparation method thereof

    CN121202510A